Transfusion medicine for pathologists : a comprehensive review for board preparation, certification, and clinical practice /: a comprehensive review for board preparation, certification, and clinical practice. (2018) - Castillo, Brian; Dasgupta, Amitava, 1958-; Klein, Kimberly (Kimberly L.); Tint, Hlaing; Wahed, Amer
No abstract available